Exploring undergraduate students’ difficulties in EFL academic writing - Atikah Wati; Kardi Nurhadi; Ahmad Lukmanul Hakim (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study aims to explore undergraduate students’ difficulties and how they cope with difficulties in EFL academic writing. Despite much research revealing the difficulties of undergraduate students in academic writing, relatively few studies implied academic writing difficulties in the higher education context. To fill this gap, this present study focused on exploring EFL students’ difficulties and how they cope with the difficulties in terms of lexical difficulties, grammar and punctuation, avoiding plagiarism, and text structure. This study used a qualitative approach with a phenomenological case study design. Three undergraduate students were recruited as participants for this study. The data were collected through interview sessions employing open-ended questions adopting a three series of interviews by Seidman (2013) consisting of thirteen questions. The result showed similarities and differences in difficulties and the ways to cope with it. The result of this research is expected to support the lecturer to consider the students’ difficulties and their ways to cope with the difficulties where it can be applied in academic writing subject. Moreover, the difficulty in academic writing is important for students to examine the effective ways to cope with difficulties to become better academic writers. Keywords: Undergraduate students; Academic writing; Academic writing difficulties